2012
DOI: 10.4209/aaqr.2012.07.0201
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an Asian Dust Storm and Southeast Asian Biomass Burning on the Characteristics of Seashore Atmospheric Aerosols in Southern Taiwan

Abstract: This study explores the effects of an Asian dust storm (ADS) and Southeast Asian biomass burning on the composition of atmospheric aerosols in the coastal area of southern Taiwan in spring 2010. Coarse and fine particles were collected using two manual dichotomous samplers (Dichots) that were equipped with Teflon and Quartz filters. The results reveal that the concentrations of PM 10 and PM 2.5 in the ADS period were about twice those before and after this. More than half of water-soluble ions in coarse partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 43 publications
(51 reference statements)
2
30
3
Order By: Relevance
“…The mercury levels in winter were generally higher than those in summer, suggesting that the height of mixing layer at these areas was lower in winter due to a relatively more stable atmosphere, which plays an important role in elevating the atmospheric mercury concentrations based on mass balance (Lindqvist et al, 1991;Burke et al, 1995;Kock et al, 2005). However, different findings observed at the Penghu Islands and selected locations in the East Asia were possibly attributed to the influences of biomass burning and mercury transport from adjacent areas in certain seasons (Nguyen et al, 2007;Nguyen et al, 2010;Chand et al, 2008;Fu et al, 2010;Tsai et al, 2012). In summary, in addition to the local sources and open burning, the concentration of TGM at the Penghu Islands was mainly influenced by the long-range transportation of air masses, as the prevailing wind direction and air mass transportation routes potentially playing the critical roles on the variation of TGM concentration in the atmosphere.…”
Section: Transportation Routes Of Tgmmentioning
confidence: 99%
See 1 more Smart Citation
“…The mercury levels in winter were generally higher than those in summer, suggesting that the height of mixing layer at these areas was lower in winter due to a relatively more stable atmosphere, which plays an important role in elevating the atmospheric mercury concentrations based on mass balance (Lindqvist et al, 1991;Burke et al, 1995;Kock et al, 2005). However, different findings observed at the Penghu Islands and selected locations in the East Asia were possibly attributed to the influences of biomass burning and mercury transport from adjacent areas in certain seasons (Nguyen et al, 2007;Nguyen et al, 2010;Chand et al, 2008;Fu et al, 2010;Tsai et al, 2012). In summary, in addition to the local sources and open burning, the concentration of TGM at the Penghu Islands was mainly influenced by the long-range transportation of air masses, as the prevailing wind direction and air mass transportation routes potentially playing the critical roles on the variation of TGM concentration in the atmosphere.…”
Section: Transportation Routes Of Tgmmentioning
confidence: 99%
“…The highest concentrations of PM 10 and PM 2.5 observed in spring were 54.60 ± 15.56 and 31.07 ± 10.59 µg/m 3 , respectively, while the lowest concentrations of PM 10 and PM 2.5 occurred in summer were 36.63 ± 8.69 and 17.70 ± 6.48 µg/m 3 , respectively. Spring and winter are two major seasons frequently blowing Asia dusts from northern China to the Penghu Islands Tsai et al, 2012), which could significantly increase the concentrations of PM 10 . Overall speaking, the concentrations of SO 2 and NO x measured at the Penghu Islands were much lower than most cities in Taiwan, indicating there are no significant highly polluted industries in the Penghu Islands.…”
Section: Backward Trajectory Simulation and Fire Mapmentioning
confidence: 99%
“…The BB plume from Southeast Asia could impact the air quality on the ground in Southern Taiwan was firstly proposed by Tsai et al (2012). Later, Yen et al (2013) suggested that a cold surge causes a downward flow that drags high-altitude BB pollutants to the ground and found that a cold surge accompanied with a cold front or a cold surge that occurred one or two days after a cold front passed Taiwan on March 9, 16, and 25 and on April 2, 7, and 13 in 2010 resulted in the deterioration of the air quality at the Hengchun ground site.…”
Section: High-altitude Bb Plume Affected the Air Quality On The Groundmentioning
confidence: 99%
“…By integrating the data already published in the literature plus those that can be searched from relevant websites, we try to further elucidate the dispersal of Fukushima-derived radiation toward the southeastern Asia region. It should be noted that, in these studies, the aerosol samples were collected by large-volume air samplers using filters similar to those described in Zhao et al (2012) and Tsai et al (2012). Therefore, we would address to the validity of our direct comparison of the datasets.…”
Section: Introductionmentioning
confidence: 99%